Design Philosophy for Buildings’ Comfort-Level Performance - Wariyatno, Nanang Gunawan; Lie, Han Ay; Hsiao, Fu-Pei; Gan, Buntara Sthenly (Advances in Technology Innovation, 2021)
The data reported by Japan Meteorological Agency (JMA) show that the fatal casualties and severe injuries are due to heavy shaking during massive earthquakes. Current earthquake-resistant building standards do not include comfort-level performance. Hence, a new performance design philosophy is proposed in this research to evaluate the quantitative effect of earthquake-induced shaking in a building. The earthquake-induced response accelerations in a building are analysed, and the response accelerations related with the characteristic property of the building are used to evaluate the number of Seismic Intensity Level (SIL). To show the indispensability of the newly proposed comfort-level design philosophy, numerical simulations are conducted to evaluate the comfort level on different floors in a building. The results show that the evaluation of residents’ comfort levels should be considered in the current earthquake-resistant building design codes.